The use of the Prospector calculator reduces antibiotic therapy in exacerbations of chronic obstructive pulmonary disease - Marcin Paprocki; Szymon Żwirowski; Krzysztof Kuziemski (Scientific Reports)
Abstract Chronic obstructive pulmonary disease (COPD) exacerbations frequently cause patient consultations in both out- and inpatient settings. Recent data suggest that only 40–60% of exacerbations are of bacterial origin and mandate antibiotic treatment. However, a reliable tool to justify prescribing antibiotics for COPD exacerbation is still lacking. This study was designed to explore the hypothesis that utilization of a novel decision-making tool called Prospector would lead to lower consumption of antibiotics and provide a more rational approach to managing COPD exacerbations versus standard therapy in patients with COPD. The study included 77 COPD patients who experienced a COPD exacerbation and were treated in outpatient settings. The Prospector group (PG) (n = 40) were treated by the study author using the Prospector calculator (a tool designed by the first author that translates: patient symptoms, exacerbation, and medical history of COPD into a decision on the use of antibiotics in COPD exacerbation treatment). Other primary care specialists treated the control group (CG) (n = 37) in the same outpatient clinic; antibiotic therapies were implemented at the physician’s discretion, most often using Anthonisen’s criteria. All other medications were administered at the physician’s discretion. Safety endpoints were set as: death, hospitalization, and number of exacerbations. Antibiotics were administered in 32.8% and 81.2% of exacerbations in the PG and CG, respectively (p < 0.0001). A comparable percentage was verified positively in both PG patient subsets: those that did and did not receive antibiotics at visit 1 (94.7% and 94.9%, respectively). Twenty-eight patients in the PG and 37 in the CG were followed for up to 35 months. Failure to recover (defined as deterioration or lack of improvement) in 30 days following exacerbation was 10.7% in the PG and 47.2% in the CG. In the CG, the failure rate was significantly higher (p = 0.0043). Hospitalization rates in the PG and the CG were 42.9% and 94.4%, respectively. In the CG, the hospitalization rate was significantly higher (p < 0.0001). COPD hospitalization rates in the PG and the CG were 17.9% and 33.3%, respectively (p = 0.1643). This preliminary study suggests that using the Prospector calculator results in markedly reduced antibiotic prescription for COPD exacerbations. No new safety signals have been identified for the method.